The influence of digital reading habits on student performance at vision college: a conceptual framework/ Nur Atikah Abdullah and Haslinda Husaini - Abdullah, Nur Atikah; Husaini, Haslinda (Faculty of Information Management, 2022)
Since the advent of digital media and the proliferation of digital resources, reading has altered tremendously. Regardless of digital reading, several concerns or variables, such as demographic characteristics, the effect of digital media and ICT, a lack of reading enthusiasm, and new reading norms during the reading COVID-19 epidemic, contribute to bad reading habits among individuals, particularly among students. The impact of digital reading habits on undergraduate achievement, especially among Vision College students, will be investigated in this study. Based on earlier research, this study has also established a conceptual framework.